DAMPAK KELUARGA BROKEN HOME TERHADAP PSIKOLOGIS ANAK - Mistiani, Wiwin (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
Broken home can also be interpreted as a family condition that is not harmonious and does not work like a harmonious, peaceful, and prosperous family because of frequent riots and disputes that lead to disputes and end in divorce. Actually children who are broken home are not only children who come from divorced parents, but also children who come from families that are not intact or not harmonious. There are many factors behind the broken home, including fights or parental fights, divorce, parent's busy life. The impact of broken home on the child's psychological, among others: Children begin to suffer from high anxiety and fear. Children feel clamped in the middle, because they have to choose between mother or father, Children often have a sense of guilt and If both parents are fighting, it allows children can hate one of their parents. Some psychologists state that the most important help a divorced parent can give is to try to reassure and convince children that they are innocent. Ensure that they do not need to feel responsible for the divorce of their parents. Another thing that needs to be done by parents who are going to divorce is to help children adjust to keep running routine activities at home. Do not force children to side with one of the parties who are bickering, and do not occasionally involve them in the divorce process. Another thing that can help children is to find other adults such as aunts or uncles, who can temporarily fill their emptiness after being left by their father or mother. That is to say, so that children feel they are getting a support that strengthens them in finding a substitute figure for a mother father who is no longer present as when there is no divorce.